Devolving responsibilities for human resources to line management? An empirical study about convergence in Europe - Wolfgang Mayrhofer; Michael Müller-Camen; Johannes Ledolter; Guido Strunk; Christiane Erten-Buch (Journal for East European Management Studies, 2004)
The lively debate about converging or diverging management practices is not yet decided. Human resource management (HRM) is no exception. Using the widely discussed issue of HR specialists handing over HR tasks to line management as an example, the article analyses whether European companies in the last decade have adopted similar HR practices and whether successful European companies are similar to each other in this respect. The results show that there is no trend towards convergence in Europe. Furthermore, various configurations of HR practices characterise successful organisations. Both results have important consequences for HR academics and practitioners, especially in the Central and Eastern European countries. – – Die umfangreiche Debatte über Konvergenz bzw. Divergenz im Management allgemein bzw. im HRM im Besonderen ist nicht entschieden. Am Beispiel der Verlagerung von Personalaufgaben von zentralen Fachabteilungen auf das Linienmanagement geht der Artikel der Frage nach, inwieweit Unternehmen in Europa im letzten Jahrzehnt ähnliche Personalpraktiken eingesetzt haben und wie sehr sich erfolgreiche Unternehmen in dieser Hinsicht ähneln. Die Resultate zeigen keine konvergierenden Entwicklungen in Europa. Weiters zeigt sich, dass erfolgreiche Unternehmen durch sehr unterschiedliche Konfigurationen von Personalpraktiken gekennzeichnet sind. Beide Resultate sind für die Personalforschung und praxis vor allem auch in den mittel- und osteuropäischen Ländern von Bedeutung.
Keywords: 650; Empirical research; Human resource management; Organisational performance; Europe; International comparative studies